Framing Analysis of the South China Sea News Conflict in the Malay Media - Das'ad Latif; Muhammad Ruslan Ramli; Ballian Siregar (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
This study examines the South China Sea conflict involving countries in the region. However, it is not limited to those bordering the South China Sea because other superpower countries are also involved, such as the US, Britain, Germany, Canada, Australia, India. The conflict garnered serious attention from Malay media such as kompas.com (Indonesia), bharian.com.my (Malaysia) and mediamediapermata.com (Brunei). This study sought to inspect how Malay media frame the South China Sea conflict using a qualitative-descriptive approach. Using Entman’s model, it focused on root causes, problem causes, moral judgments, and recommendations. As a result, the three media saw China's claims to the South Sea and its abundant natural resources as the root of the problem. Bharian.com.my added that another root of the problem is China's hegemony in the South Seas. For causes of the problem, they agreed on China’s over-aggression and their patrol warships in the South China Sea. In addition, kompas.com and bharian.com added China's policy requiring foreign ships to report if they pass into the South China Sea. Furthermore, kompas.com also saw the different interests of ASEAN countries and the formation of the AUKUS alliance as the cause of the problem. In terms of moral judgments, they agreed on the need to maintain peace, order and security in the South China Sea. As for the recommendation aspect, they encourage compliance with UN conventions. Then, kompas.com and bharian.com.my also considered the importance of diplomacy at the negotiating table.